The Effect of Implementing the Technology Acceptance Model (Tam) on Shopping Intention (Behavioral Intention) Using Paylater - Herowati, Erlina (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research analyzes the Technology Acceptance Model theory (TAM) in shopping behavior using Paylater. The purpose of this research is to determine the influence of perceived usefulness and perceived ease of use on shopping interest using Paylater (behavioral intention). Respondents from this research are people who know E-Commerce and know the Paylater payment tool. After testing, the results of this research are that perceived usefulness has a significant positive effect on shopping interest using Paylater (behavioral intention), this is shown by the level of significance value of 0.046. Meanwhile, perceived ease of use does not have a significant effect on shopping interest using Paylater, behavioral intention of Paylater users. The behavioral intention of Paylater users is explained by the variables Perceived usefulness and Perceived ease of use of 7.4%, the rest is explained by other variables outside this research.